The Effect of the Teams Games Tournament (TGT) Cooperative Learning Model on the Mathematics Learning Outcomes of Fourth-Grade Students at SD Inpres 5 Lolu - Gusti Putu Indra Kurniawan; Zulnuraini Zulnuraini; Nurul Kamisani; Azizah Azizah; Ammar Abdullah Joni Guci (Journal of Educational Sciences, 2026)
This study aims to analyze the effect of the Teams Games Tournament (TGT) cooperative learning model on the mathematics learning outcomes of fourth-grade students at SD Inpres 5 Lolu, specifically on the topic of fractions. The research used a quantitative approach with a One-Group Pretest–Posttest Design involving 20 students as the experimental sample. Data were obtained through pretest and posttest instruments and analyzed using descriptive statistics, the Shapiro–Wilk normality test, the Paired Sample t-test, and the N-Gain test with the assistance of SPSS Statistics. The results revealed a substantial improvement in students’ cognitive abilities after the application of the TGT model. The average pretest score of 22.5 increased to 81 on the posttest, yielding a mean gain of 58.5 points. The Paired Sample t-test produced a significance value of <0.001, indicating a statistically significant effect of the TGT model on learning outcomes. Furthermore, the N-Gain value of 0.7663 categorized the improvement as high. These findings indicate that the TGT model is effective in enhancing students’ understanding of fractions, increasing engagement, and creating a more interactive learning environment. Thus, TGT can be considered an innovative alternative learning strategy for improving mathematics outcomes at the elementary school level.